2019
DOI: 10.1186/s12862-019-1488-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of conservation of spliceosomal intron structures and spliceosome divergence in representatives of the diplomonad and parabasalid lineages

Abstract: Background Two spliceosomal intron types co-exist in eukaryotic precursor mRNAs and are excised by distinct U2-dependent and U12-dependent spliceosomes. In the diplomonad Giardia lamblia , small nuclear (sn) RNAs show hybrid characteristics of U2- and U12-dependent spliceosomal snRNAs and 5 of 11 identified remaining spliceosomal introns are trans -spliced. It is unknown whether unusual intron and spliceosome features are conserved in other dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…Giardia has minimal spliceosomal machinery as well as canonical nucleotide signatures in 6 cis-spliced genes and 3 trans-spliced genes identified so far [3][4][5][6]8,9]. Previous bioinformatic analysis has revealed the presence of minimal spliceosomal machinery; the conserved snRNAs and major snRNA-associated proteins in Giardia [3,26]. Further, Vanessa Gomez et al, showed the in vivo expression of core spliceosomal proteins SmB, SmD3, SmD1, SmD2, SmE, SmF in a complex with U1, U2 and U4 snRNAs [13].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…Giardia has minimal spliceosomal machinery as well as canonical nucleotide signatures in 6 cis-spliced genes and 3 trans-spliced genes identified so far [3][4][5][6]8,9]. Previous bioinformatic analysis has revealed the presence of minimal spliceosomal machinery; the conserved snRNAs and major snRNA-associated proteins in Giardia [3,26]. Further, Vanessa Gomez et al, showed the in vivo expression of core spliceosomal proteins SmB, SmD3, SmD1, SmD2, SmE, SmF in a complex with U1, U2 and U4 snRNAs [13].…”
Section: Plos Neglected Tropical Diseasesmentioning
confidence: 99%
“…1998; Hudson et al. 2019; Madhani and Guthrie 1992; Mitrovich and Guthrie 2007; Stark et al. 2015), and the U2 snRNA candidate from P .…”
Section: Resultsmentioning
confidence: 99%
“…2; File S4). The U2 snRNA, which recognizes and interacts directly with nucleotides adjacent to the branch point adenosine, is highly conserved in structure across diverse eukaryotes (Fast et al 1998;Hudson et al 2019;Madhani and Guthrie 1992;Mitrovich and Guthrie 2007;Stark et al 2015), and the U2 snRNA candidate from P. purpureum is no exception (Fig. 2B).…”
Section: Many Transcripts In Porphyridium Purpureum Are Not Splicedmentioning
confidence: 99%
“…The results from the BLAST searches were further screened by analyzing domain content (HMMsearch, HMMer 3.1b2 – default parameters), size comparisons against human protein sequence length (within 25% variation), and reciprocal best-hit BLAST searches (RBH) to the query proteome (Bork et al, 1998; Johnson et al, 2010; Tatusov et al, 1997). To avoid bias in protein domain content, domains used for HMM searches were defined as described (Hudson et al, 2019). Briefly, a conserved set of domains for each spliceosomal protein was assembled by using only those domains present in all three of the human, yeast, and Arabidopsis orthologs.…”
Section: Methodsmentioning
confidence: 99%